Dynamics of Employee Turnover Intention and The Role of Organizational Commitment as A Moderator - Alimu, Farah Sabilla (Lembaga Penerbitan Universitas Esa Unggul, 2025)
This research is based on the results of initial observations that inform the actual employee turnover in 2023 to 2024. The purpose of this study is to empirically reveal job satisfaction, personality and perception of organizational support towards turnover intention and organizational commitment as a moderation variable. The type of research is included in the quantitative with a cross sectional study design. The population used is staff in nursing, patient relations, accounting and finance, public services, quality departments, pharmacy, growth and development clinics, and laboratories which until the beginning of 2024 totals 355 personnel. The sampling technique uses purposive sampling, so that the number of samples is determined to be 77 respondents. The data collection technique uses a questionnaire, and the analysis method uses the three box method and PLS-SEM analysis. The results of the analysis prove that job satisfaction has no effect on turnover intention, but the perception of organizational support has a negative effect on turnover intention, while personality and organizational commitment have a positive effect on turnover intention. Organizational commitment moderates the relationship between job satisfaction and personality to tunover intention, while organizational commitment is unable to moderate the relationship between organizational support perception and turnover intention